Koncepce rozvoje geoinformačních dovedností ve výuce na základních a středních školách - Mísařová, Darina (Masaryk University Press, 2021)
Title in English: The concept of developing geoinformatics skills in teaching at primary and secondary schools This conceptual monograph responds to insufficient support for developing geoinformation skills in Czech lower and upper secondary schools. It aims to create an interconnected system for developing geoinformation skills in teaching in lower and upper secondary schools, emphasizing the implementation of GIS tools and proposing principles for the development of geoinformation skills in teaching. For this purpose, a matrix of learning tasks is created, arranged according to individual geoinformation skills - reading, selection, use, creation, and sharing. The monograph is intended mainly for pre-service and in-service geography teachers at lower and upper secondary schools, the leaders of school educational programmes, and teachers in non-formal education. The monograph, including learning tasks and other materials, is available online at https://gitdoskol.ped.muni.cz.